2015
DOI: 10.1007/jhep08(2015)058
|View full text |Cite
|
Sign up to set email alerts
|

On single and double soft behaviors in NLSM

Abstract: Abstract:In this paper, we study the single and double soft behaviors of tree level offshell currents and on-shell amplitudes in nonlinear sigma model (NLSM). We first propose and prove the leading soft behavior of the tree level currents with a single soft particle. In the on-shell limit, this single soft emission becomes the Adler's zero. Then we establish the leading and subleading soft behaviors of tree level currents with two adjacent soft particles. With a careful analysis of the on-shell limit, we obtai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…In the case of NLSM-type theories also the double-soft behavior has been studied [6,[22][23][24][25][26]. In particular, it has been shown that the amplitude for the emission 1 As discussed in ref.…”
Section: Jhep09(2017)001mentioning
confidence: 99%
“…In the case of NLSM-type theories also the double-soft behavior has been studied [6,[22][23][24][25][26]. In particular, it has been shown that the amplitude for the emission 1 As discussed in ref.…”
Section: Jhep09(2017)001mentioning
confidence: 99%
“…A complete classification of all possible soft theorems at various orders of the soft expansion has not appeared, although some discussion of it exists [79,80]. New soft theorems at various orders have recently been discovered in nonabelian gauge theories [20,77,81,82], supersymmetric theories [83][84][85], nonlinear sigma models [86], string theories [76,[87][88][89][90][91][92][93], and in other contexts [94][95][96][97][98]. Interesting universal structures are known for limits when two or more external particles are taken to be soft.…”
Section: Echoing Trianglesmentioning
confidence: 99%
“…. , 2n) where the first soft pion is adjacent to the off-shell leg (see [7] for discussion about l = 1, i = 0).…”
Section: Berends-giele Recursion Approachmentioning
confidence: 99%